Physiotherapy as a first point of contact in general practice: A solution to a growing problem? - Goodwin, Rob W.; Hendrick, Paul (Cambridge University Press, 2016)
Aim: To evaluate the clinical effectiveness, patient satisfaction and economic efficacy of a Physiotherapy Service providing musculoskeletal care, as an alternative to GP care. Background: There is a growing demand on general practice resources. A novel '1st Line Physiotherapy Service' was evaluated in two GP practices. Physiotherapy, as a first point of contact, was provided as an alternative to GP care for patients with musculoskeletal complaints. Participants: A convenience cohort sample of over 500 patients with a musculoskeletal complaint were assessed within the Physiotherapy Service. For the economic evaluation a cohort of 100 GP patients was retrospectively reviewed. Method: Clinical outcome measures were collected at assessment, 1-month and 6-months following assessment. Patient satisfaction was collected at assessment. An economic evaluation was undertaken on the Physiotherapy cohort of patients and compared to a retrospective cohort of patients (n=100) seen by a GP. This evaluation considered the healthcare perspective (primary and secondary care). Societal issues such as absence from employment were not considered. Results: There were no adverse events associated with the Physiotherapy Service. Patients reported high levels of satisfaction with the Physiotherapy Service. Patients managed within the 1st Line Physiotherapy Service demonstrated significant clinical improvements (EQ-5D-5L, Global Rating of Change) at the 6-month point. There was a statistically significant difference in favour of the Physiotherapy groups using a nonparametric bootstrap test £611.19 (95% bootstrap CI; £1002.93, £290.95) and £330.99 (95% bootstrap CI £671.85, £63.11) respectively). Conclusion: The Physiotherapy service appears to provide a safe and efficacious service as an alternative to usual GP care. The service is well received by patients. There appear to be significant financial implications to the health economy. Physiotherapists, as a first point of contact for patients with MSK related complaints, could contribute to the current challenges faced in primary care.